Process for Producing A Cyclic Acetal In A Heterogeneous Reaction System - FEORD DAMIAN; KURZ KLAUS; JONI; LINGNAU JURGEN; HAUBS MICHAEL (2018)
A process for producing a cyclic acetal is disclosed. According to the process, a formaldehyde source is combined with an aprotic compound and contacted with a heterogeneous catalyst which causes theformaldehyde source to convert into a cyclic acetal such as trioxane. The catalyst, for instance, may comprise a solid catalyst such as an ion exchange resin. In one embodiment, the process is used for converting anhydrous formaldehyde gas to trioxane. The anhydrous formaldehyde gas may be produced form an aqueous formaldehyde solution by an extractive distillation. 公开了用于生产环状缩醛的方法。根据本方法，甲醛来源与疏质子化合物组合并且与非均相催化剂接触，其导致甲醛来源转化成环状缩醛，例如三氧杂环己烷。例如，催化剂可以包括固体催化剂，例如离子交换树脂。在个实施方案中，本方法为用于将无水甲醛气体转化成三氧杂环己烷的方法。可以通过提取蒸馏由甲醛水溶液生产无水甲醛气体。